Comparing the Impact of Individual‐ and Team‐Based ChatGPT Collaboration on High School Students' Cognitive Competencies in Programming Education. - Hussein, Mahmood H.; Aldeeb, Fatimah Husayn Amir; Sulaiman, Nor Lisa; Elaish, Monther M. (Journal of Computer Assisted Learning, 2026)
Background: Increased research attention has recently been given to the topic of programming education, due to its significance in promoting students' critical thinking, complex problem‐solving, creativity, and communication skills—commonly known as the '4Cs'. In particular, collaborative programming has been recognised as a promising instructional approach to promote students' cognitive competencies in programming education. However, simply offering students opportunities to collaborate will not necessarily improve their 4Cs. Thus, the potential of ChatGPT has been considered to address the drawbacks of conventional collaborative programming and to improve students' cognitive capabilities. Objective: To ascertain whether ChatGPT is a viable instructional tool in collaborative programming, this study proposes the ChatGPT‐CIDI (Clarify, Ideate, Develop and Implement) learning model. Methods: A quasi‐experimental method was implemented, wherein 61 students from two 12th‐grade classes participated. One class (Group One) (n = 28, Mage = 17.25) was assigned to individual‐based collaboration using the ChatGPT‐CIDI model, while the second class (Group Two) (n = 33, Mage = 17.61) undertook team‐based collaboration using the same model. Results and Conclusion: The empirical results demonstrated that this approach significantly improved students' critical thinking in Group One (individual‐based), compared to Group Two (team‐based). However, neither group experienced significant improvement in their complex problem‐solving, creativity, or communication skills. This study concludes with implications for research and practice, while also indicating the research limitations to determine future research directions. Lay Description: What is already known about this topic ○In the age of AI, programming education is at the center of research attention.○Collaborative programming has been identified as a viable instructional method to foster students' cognitive competencies.○ChatGPT could address the limitations of the conventional collaborative programming method.What this paper adds ○A ChatGPT‐CIDI model is designed. The effectiveness of this model is investigated in different collaboration modes, namely, individual‐ and team‐based collaboration.○The students assigned to individual‐based collaboration made significant gains in their critical thinking compared to their peers in the team‐based collaboration group.○Regardless of their method of collaborating with the ChatGPT‐CIDI model, the students experienced no significant improvement in their complex problem‐solving, creativity, or communication skills.Implications for practice and/or policy ○This study is a step forward in the process of adopting hybrid intelligence in K‐12 educational settings.○Researchers and educators are advised to investigate the variables that can influence students' creativity while interacting with ChatGPT in programming education.○When ChatGPT is incorporated into the learning activities for programming education, researchers and educators need to consider students' agency and facilitate organic communication among them○The developers of GenAI are urged to incorporate explanatory mechanisms into the output of their chatbots, in order to facilitate the development of students' problem‐solving skills.